A Translation Analysis of Derivative Noun in The Giver into Sang Pemberi by Ariyantri Eddy Tarman - Pramitasari, Djati, Dr. Dwi Haryanti, M.Hum, Drs. Sigit Haryanto, M.Hum (2015)
The objectives of this study are to classify the translation shift variations of derivative noun and to describe the equivalence translations of derivative noun. This research is descriptive qualitative research. The data are in form of sentences containing derivative noun taken from The Giver novel and its translation Sang Pemberi. The technique of collecting data is documentation. The data are analyzed using comparing method between the source and the target language. The first results of the data analysis show that from 500 data there are 12 translation shift variations of derivative noun.They are derivative noun marked by their suffixes translated into (1) noun 366 data or 73,2%, (2) noun+ pronoun -mu 1 data or 0,2%, (3) noun+ pronoun -nya 10 data or 2%, (4) adjective 10 data or 2%, (5) adverb 2 data or 0,4%, (6) verb 22 data or 4,4%, (7) adjective phrase 1 data or 0,2%, (8) adverb phrase1 data or 0,2%, (9) noun phrase 31 data or 6,2%, (10) verb phrase 5 data or 1%, (11) from plural into singular 47 data or 9,2%, and (12) not translated 4 data or 0,8%. The second results show that the data of translation shift variations of derivative noun are included in equivalent translation. There are 499 data or 99,8% equivalent and only 1 datum or 0,2% not equivalent